Teaching history: pedagogical practices and complexities in upper secondary schools of Ethiopia - Sisay Awgichew Wondemtegegn; Enguday Ademe Mekonnen (College of education, Bahir Dar University, 2023)
This study examined the pedagogical practices and complexities in teaching history in the upper secondary schools of Ethiopia. The study employed descriptive case study research design. Data were obtained from nine key informants, textbooks, syllabi, and other publications. Interview and document review were used as principal data collection tools. Data were analyzed using qualitative narrative approach. The findings revealed that teachers frequently use lecture, explanation, and discussion as the main methods of teaching. Debate, inquiry, justification, and multiple-interpretation methods were not properly used by teachers, and are rarely incorporated in the textbooks. Instructional activities such as what and why questions, explanations, and discussion questions appeared often in the prescribed textbooks. Moreover, the grand historical narratives and counter-narratives apparently made Ethiopia's history turbulent and complex as such narratives are influenced by political factors. Furthermore, interview respondents revealed that phrases incorporated in the Ethiopian history publications such as 'Assimilation', 'Amharanisation', 'Colonization', 'Restoration', and 'Oromization' are politically motivated discourse than academic concepts and they create complexities in the Ethiopian historical narratives. Besides, content overload, over emphasis on the country`s political and military histories than social and economic history, and lack of consensuses among politicians make the teaching of history very complex.